Isolasi dan Identifikasi Eschericia coli O157:H7 dari Babi, Sapi dan Ayam yang Menunjukkan Gejala Diare - Elisabet Tangkonda (JURNAL KAJIAN VETERINER, 2019)
Escherichia coli is a bacterium found in the intestines of humans and animals. Most strains of Escherichia coli are harmless. However, some strains, such as Enterohaemorrhagic Escherichia coli (EHEC), can cause a disease transmitted to humans through contaminated food. Enterohaemorrhagic Escherichia coli produce toxins, known as verotoxin thus also known as Verocytotoxin-producing E. coli (VTEC). The aim of this study was to isolate and identify Escherichia coli O157:H7 from pigs, cattle and chickens. Samples were taken from pigs, cattle and chickens with diarrhea and identified by microbiological diagnostic. The result reveal, 18 of the 18 pig samples, 17 of 30 samples of cattle and 34 of 46 samples of chicken identified as E. coli O157:H7 with prevalence 100%, 56.6% and 73.9% respectively.